Effect of Edible Coating and Storage to Shelf Life of Orange Fruit during Storage - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Orange fruit has high moisture content and nutrient composition make this fruit more susceptible to sofening, browning, or color change and microbial contaminations. It rapidly deteriorates during handling, transport and storage. Edible coatings are widely used for extension of shelf life of fruits and vegetables by reduction of moisture loss and gas exchange as well as reduction of the physiological disorders. The objective of the present study was to identify the effect of different CMC concentrations (1%, 2%, 3%, 4%, 5%) and storage temperature (8 o C, 12 o C, 16 o C, 20 o C) to the weight loss, firmness, total soluble sugar and ascorbic acid in orange fruits during preservation. Moreover, shelf life (0 day, 7 days, 14 days, 21 days and 28 days) of orange fruit in storage also clarified. Results demonstrated that CMC 4% and storage temperature 8 o C could maintain orange fruit quality for 28 days without any deterioration.Keywords: Edible Coating, Orange Fruit, Shelf Life